Inovasi Produk UMKM ‘CEMARA’ melalui FGD untuk Penguatan Desa Wisata Winduraja - Syaroh Amaliyah, Rizqi; Bambang Setiawan; Noviani; Erna Sulistiani; Nazwa Prillia Marshanda; Berliani Jannati Firadusi; Tsaniyah Fatimatuzzahro; Raden Noviyanti; Afiyah Armina Ramadhan; Annisa Rahmani Dewi; Ateh Zakiah Sopiah; Ilvi Nur Aulia Heryadi; Irma Fitriyani; Rosa Maelani; Septi Laila Nurpadilah; Tiara Kirani Rahayu (ACITYA BHAKTI, 2025)
The snack-based MSMEs in Winduraja Village possess significant economic and tourism potential but face challenges in product innovation and packaging. This community service activity aims to develop innovative products based on MSMEs as a local culinary identity and as part of a strategy to strengthen the village tourism sector. A participatory-collaborative approach was employed, involving MSME actors and village institutions through stages of observation, needs analysis, product design, and a Focus Group Discussion (FGD). Local products such as comring, glass chips, and tempeh chips were developed with new flavor variants, attractive packaging, and names reflecting Sundanese cultural identity. The results include the creation of a distinctive village culinary brand and enhanced synergy among stakeholders. Participatory evaluation indicated increased MSME involvement, a sense of ownership, and encouragement of sustainable production initiatives. This program demonstrates that product innovation, combined with the FGD approach, can strengthen MSME competitiveness and build the village’s image as a community-empowered tourism destination.